Analysis Producer Behavior (Boarding House Owners) Towards the Implementation of Hotel Tax Categorized for Boarding Houses (Case Study Watugong, Malang) - Eka Putra, Tri Soewandi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Taxes become a state obligation and devotion as well as the active role of the state and members of the public. Regional autonomy serves to organize and manage the potential of existing resources in the region. Under the policy of each region will earn revenue (PAD) which will be used to finance regional development. One source of revenue that can be obtained is through the hotel tax. Malang can be known as a city of education, which has a number of state universities and private colleges are well known in Indonesia. This makes the number of entrants that the majority of students are in Malang, so that more and more businesses boarding house in Malang area. Business boarding houses belong to the category of hotel tax with the Local Government Regulation No. 16Year 2010 Malang. By applying these rules will emerge a variety of different behavior of producers (Owner Boarding House) and consumers (Tenants Boarding House). This study will analyze the behavior of consumers and producers against the regulation by using qualitative research methods with descriptive research. The results of this study the behavior of the manufacturer of the taxes charged to the customer with a percentage of 50%, the tax charged to producers by 20%, the reduction in the facility by 10%, and increase the number of rooms by 20%. Consumer behavior that dorm room tenant willing to move to another boarding house as many as 11 people and tenants dorm room who was not willing to move as many as nine people. Consumers who do not wish to move because they are already comfortable with boarding at the moment, so that consumers are not concerned about the increase in rental prices boarding, but there are some consumers do not increase the price of rental boarding house.Keywords: Consumer, Boarding House Tax, Behavior, Producer